SUPPLY CHAINS RESILIENCE, POSSIBLE TRAJECTORIES OF INTERNATIONAL PRODUCTION AND THE EUROPEAN UNION'S RESPONSE IN THE CONTEXT OF THE COVID-19 PANDEMIC - da Silva, Janaína Conceição [UNESP]; Vale, Mário (My University, 2023)
The various stoppages and shortages observed in the context of the COVID-19 pandemic have exposed a series of contradictions and vulnerabilities, especially in the way production structures are organized territorially on a global scale. Although such disruptions are not unprecedented, the facts have drawn attention to the need to adopt strategies to make them more resilient. Based on the recent literature on the subject, this article aims to present a reflection on the content of reshoring, diversification and sustainability strategies, looking at their definitions (conceptual and practical meanings), complexities, challenges and implications for the economy and the territory. To complement the theoretical discussion, we will illustrate how these strategies are being incorporated into official documents relating to the new European industrial strategy. In methodological terms, bibliographical research and documentary research were carried out. Among the documents analyzed, the communications prepared by the European Commission in 2020 and 2021 stand out. Preliminary results show that the reallocation of fixed assets has several complexities and barriers, making diversification a less costly and more feasible solution in the short and medium term. In the European Union, in addition to diversification, sustainability has represented an important and necessary financial investment opportunity.
RESILIENCIA DE LAS CADENAS DE SUMINISTRO, POSIBLES TRAYECTORIAS PARA LA PRODUCCIÓN INTERNACIONAL Y LA RESPUESTA DE LA UNIÓN EUROPEA EN EL CONTEXTO DE LA PANDEMIA DEL COVID-19
RESILIÊNCIA DAS CADEIAS DE ABASTECIMENTO, POSSÍVEIS TRAJETÓRIAS DA PRODUÇÃO INTERNACIONAL E A RESPOSTA DA UNIÃO EUROPEIA NO CONTEXTO DA PANDEMIA DA COVID-19
Keywords: COVID-19 pandemic; diversificación; diversification; diversificação; new european industrial policy; nova política industrial europeia; nueva política industrial europea; Pandemia da COVID-19; Pandemia de COVID-19; relocalización; relocalização; reshoring; sostenibilidad; sustainability; sustentabilidade